REGIONAL SPECIFICS OF CARDIOVASCULAR MORBIDITY AND MORTALITY - M. G. Moskvicheva; S. A. Belova; S. L. Kremlev; M. I. Karpova; N. А. Samsonova (Кардиоваскулярная терапия и профилактика, 2016)
Aim. To do comparative research  on the structure, level and dynamics of morbidity by presentation  rate and mortality from cardiovascular causes (CVD) of Chelyabinskaya Region inhabitants during ten years period — 2005-2014yy.Material and methods. The area  of the study was Chelyabinskaya region  — one  of the  economically largest  regions  in Russia.  Data sources  were official data  of Federal Statistics  service of RF, reports and  accountability  sheets   from  medical  institutions  during  2005- 2014yy.Results. In mortality from CVD structure  from CVD the leading causes are ischemic heart disease  (IHD) and cerebrovascular diseases (CeVD). During the period of study there  was found a growth of general  and primary morbidity by admittance  for CVD. In the structure  of general morbidity by admittance for CVD during last 10 years IHD is the leading, in the structure  of general  morbidity by admittance  — CeVD. For the period studied, there was decrease of mortality from CVD by 22,7%, incl. 6,3% for IHD, and 1,7 times for CeVD.Conclusion. Regardless  positive tendencies  of last years, Chelyabinskaya  region  continues  to be  the  region  with high level of mortality from CVD. The revealed patterns  of dynamics and structure of morbidity and mortality from CVD dictate the necessity of elaboration of the interventions for improvement of medical care for the patients with cardiovascular diseases at the level of regions.